Лідерство i менеджмент в умовах глобальної конкуренції: комплементарність та синергія - Пойда-Носик Ніна; Poyda-Nosyk Nina; Pojda-Noszik Nina; Черленяк Іван; Cherleniak Ivan (Навчально-науковий інститут євроінтеграційних досліджень ДВНЗ "УжНУ", 2021)
Резюме. Статтю присвячено дослідженню таких феноменів, як комплементарність, синергія, рефлексія у процесах лідерства та менеджменту. Розкрито актуальний зміст поняття «комплементарність» у контексті проблеми взаємодії лідерства та менеджменту. Виділено такі простори ідентифікації, як когнітивний, структурно-функціональний, процесний. Обґрунтовано необхідність впровадження самонавчання як методу швидкої адаптації до викликів турбулентності ринкового середовища та підстави для розвитку компонент конкурентоспроможності, яке має відбуватися у формі комплексної діяльнісно-інформаційної рефлексії. Позитивний рефлексивний зв’язок між руслом лідерства та руслом менеджменту в руслі еволюції організації викликає ефект колективного емоційного інтелекту послідовників, забезпечуючи цим зростаючу синергію факторів конкурентоспроможності бізнесу сучасної фірми.

Abstract, The article is devoted to the study of such phenomena as complementarity, synergy, reflection in the processes of leadership and management. Methodology and research methods: hypothetical-deductive approach, historical analysis, comparative analysis, abduction method. The substance of the complementarity concept in the context of the problem of interaction between leadership and management in nowadays conditions has revealed. The following spaces of identifi cation are distinguished: 1) cognitive (discovery, understanding, explanation), 2) structural-functional (forces, interactions, structures, distributions, forms); 3) processes (transformations, evolution, algorithms, genetic-algorithmic networks). It is shown that the economic concepts “assets”, “resources” and “potential” can be successfully applied to the issues of management and leadership with the appropriate modifi cation of the content. Thus, the system-forming components of the construct “asset” in management and leadership are such types of capital as organizational, social and humanitarian, which are formed on the basis of morality, etiquett e, scientific knowledge, organizational memory, corporate culture, quality of human resources.It is substantiated that in the context of the problem of complementarity of the areas of leadership and management refl ection is a connection of three or more events: 1) the existence of the actor’s actions, 2) the existence of co-actor actions, 3) fi xation of the conclusion actor for his actions. It is on this complex basis that architectural complementarity and confrontation emerges between elements of two orthogonal classes of the internal structure of the system-process of interaction between management and leadership. The conclusion is substantiated that eff ective self-training of the personnel as the basis for development of fi rm competitiveness components should take place in the form of complex activity-information reflection. With a positive refl exive relationship between leadership and management in line with the evolution of the organization, there is an effect of collective emotional intelligence of followers. This generates the effect of positive multichannel complementarity. Complementaries are the emotional intelligence of leaders and emotional intelligence of followers, rational and emotional intelligence of the leaders themselves. The rational intelligence of leaders, managers and key personnel complement each other. All this together gradually provides a growing synergy of competitiveness factors for modern businesses.
Leadership and management in the conditions of global competition: complementarity and synergy
Редакційна колегія: http://geopolitics-of-ukraine.uzhnu.edu.ua/about/editorialTeam Зміст: http://geopolitics-of-ukraine.uzhnu.edu.ua/issue/view/14557
Keywords: лідерство; менеджмент; конкурентоспроможність; комплементарність; рефлексія; синергія; leadership; management; competitiveness; complementarity; reflection; synergy